Effects of chronic hypoxia on the gene expression profile in the embryonic heart in three Chinese indigenous chicken breeds (Gallus gallus) - Li, Xiaofeng; Abdel-Moneim, Abdel-Moneim Eid; Hu, Zhongze; Mesalam, Noura M.; Yang, Bing (Frontiers in Veterinary Science, 2022)
Hypoxia exposure (HE) has adverse impacts on the embryonic development of chicken, whereas the mechanism underlying the tolerance of chicken heart to HE during embryo development in birds is still unclear. Therefore, this study was conducted to elucidate differentially expressed genes (DEGs) and the signaling pathways linked to chronic hypoxia stress. Thus, the mRNA expression microarray GSE12675 was downloaded from Gene Expression Omnibus database. GSE12675 included twelve embryonic heart samples in hypoxia and normoxia of three Chinese indigenous chicken breeds [Shouguang (SG), Tibetan (TB) and Dwarf Recessive White (DRW) chickens] with four per breed. A total of 653 to 714 breed-specific DEGs were detected in each pairwise comparison. Gene ontology enrichment indicated that those DEGs were mainly involved in biological processes, including vasoconstriction, cell differentiation, the positive regulation of vasoconstriction, and the regulation of systemic arterial blood pressure (BP) by vasopressin, et al. Kyoto Encyclopedia of Genes and Genomes enrichment revealed the DEGs were mainly enriched in MAPK, PPAR, insulin, ECM-receptor interaction (ERI), and adrenergic signaling in cardiomyocytes, et al. Moreover, forty-eight genes such as SGCD, DHRS9, HELQ, MCMDC2, and ESCO2, might contribute to the heart tolerance in HE. Taken together, the current study provides important clues for understanding the molecular mechanisms of the tolerance of heart to HE during embryonic period in chicken.